A RARE CASE OF SUPERFICIAL LEIOMYOSARCOMA. SOFT TISSUE RECONSTRUCTION OF LOWER LIMB FOLLOWING ONCOLOGY EXCISION - Langat, Adriana Sigang; Cheng, Chai Siew; Luen, Koh Khai (International Journal of Allied Health Sciences, 2021)
Superficial leiomyosarcoma is a rare, malignant smooth muscle tumour of the skin which most commonly affects the extremities. Surgical excision has been the standard of care for superficial leiomyosarcoma. With the combination of oncological surgery with reconstructive surgery, along with the introduction of radiotherapy, this has led towards better tumour control and preservation of limb function. Often enough, soft tissue tumour excision results in large anatomical soft tissue defects with exposure of vital structures, necessitating soft tissue reconstruction with vascularized tissue transfer. Free anterolateral thigh (ALT) flap is a reliable and versatile flap with broad clinical applications in soft tissue coverage. Here we report a case of a 58-year-old lady who presented with one year history of high grade leiomyosarcoma over right calf. Clinically, there is a fungating mass with central ulceration measuring 9 X 9 cm over the medial aspect of her right calf. She underwent multidisciplinary surgery which involved the orthopaedic oncology team and plastic and reconstructive surgery team. Wide local excision of right calf leiomyosarcoma with oncology margins was performed, leaving a defect size 18 x 19 cm over medial aspect of posterior right calf, exposing medial gastrocnemius muscle and tibia bone. Immediate soft tissue coverage was performed using free ALT flap. The flap is raised based on two perforators from the descending branch of the lateral circumflex femoral artery. Post operatively, patient had improved outcome and aesthetics. She was able to ambulate without support 2 months after she was discharged home. ALT flap is a versatile flap and is able to shape and provide large skin for soft tissue coverage for large defect. Keywords: Leiomyosarcoma, lower limb, ALT flap, lower limb reconstruction